Performance of abiotic stress-inducible synthetic promoters in genetically engineered hybrid poplar (Populus tremula × Populus alba) - Yang, Yongil; Shao, Yuanhua; Chaffin, Timothy A.; Lee, Jun Hyung; Poindexter, Magen R.; Ahkami, Amir H.; Blumwald, Eduardo; Stewart, C. Neal (Frontiers in Plant Science, 2022)
Abiotic stresses can cause significant damage to plants. For sustainable bioenergy crop production, it is critical to generate resistant crops to such stress. Engineering promoters to control the precise expression of stress resistance genes is a very effective way to address the problem. In a previous project, we synthesized 6 osmotic-responsive promoters (SD9-1, SD9-2, SD9-3, SD13-1, SD18-1, and SD18-3) from poplar transcriptome data using a de novo DNA-motif-detecting algorithm. Their stress inducibility was identified in water-deficit and salt treatment assays using poplar leaf mesophyll protoplast transformation and agroinfiltration of Nicotiana benthamiana leaves. In this study, these 6 SD synthetic promoters were stably transformed into the Populus tremula  Populus alba hybrid poplar (INRA 717-1B4) in which GFP inducibility was screened under osmotic stress conditions. Of 6 transgenic poplar lines each harboring a different synthetic promoter, three lines (SD18-1, 9-2, and 9-3) had significantly induced GFP expression in both salt and osmotic-stress treatments. Each synthetic promoter employed heptamerized repeats of specific cis-regulatory elements. The entire SD9 motif that was heptamerized did not result in higher GFP synthesis than the shorter promoters consisting of heptamerized SD9-1, 9-2, and 9-3 (partial SD9) motifs. This result implies that shorter synthetic promoters (~50 bp) can be used for versatile control of gene expression in transgenic poplar. The tested synthetic promoters will be useful tools to engineer stress-resilient bioenergy tree crops in the future.